2005
DOI: 10.1097/00042728-200506000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Serum Iron and Matrix Metalloproteinase-9 Variations in Limbs Affected by Chronic Venous Disease and Venous Leg Ulcers

Abstract: BACKGROUND. Severe chronic venous disease (CVD) is characterized by both dermal hemosiderin accumulation and matrix metalloproteinase (MMP) hyperactivation. The iron-driven pathway is one of the recognized mechanisms of MMP hyperactivation. OBJECTIVE. To investigate the potential consequences of leg hemosiderin deposits on both iron metabolism and activation of MMPs.METHODS. We contemporaneously assessed the following in the serum of the arm and ankle veins of 30 patients (C4-6) with CVD and 14 normal subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Iron overload and its causal HFE genetic variations have been associated with the development of varicose veins [58]. Mechanistically, iron overload induces oxidative stress and the hyperactivation of matrix-degrading enzymes [59]. Other significant mineral-outcome relationships are also worth mentioning.…”
Section: Discussionmentioning
confidence: 99%
“…Iron overload and its causal HFE genetic variations have been associated with the development of varicose veins [58]. Mechanistically, iron overload induces oxidative stress and the hyperactivation of matrix-degrading enzymes [59]. Other significant mineral-outcome relationships are also worth mentioning.…”
Section: Discussionmentioning
confidence: 99%
“…When stratified for CEAP classification, those with stage 5–6 disease had significantly higher iron levels in the leg than those with CEAP 4 (86 vs 65 mg/100 mL; P < .0004). Other iron parameters were also significantly higher in the legs than in the arms of affected patients, %total iron binding capacity (TIBC) (24 vs 22%; P = .002), and ferritin (125 mg/100 mg vs 119 mg/100 mL; P = .0001); however, TIBC and transferrin did not show any significant difference …”
Section: Resultsmentioning
confidence: 90%
“…MMP-1, -2, -3, -9 and -12 activity has been detected in chronic human models of venous hypertension (Buján J et al, 2000; Sansilvestri-Morel P et al, 2007; Sansilvestri-Morel P et al, 2005; Pascarella L et al, 2005; Woodside KJ et al, 2003; Zamboni P et al, 2005). In the current model there is insufficient time for de-novo synthesis of new MMPs, and likely both MMP-8 and MMP-1/-9 are already constitutively expressed.…”
Section: Discussionmentioning
confidence: 99%
“…MMPs are also involved in the regulation of apoptosis (Egeblad, M et al, 2002). A number of studies have suggested that MMPs, especially MMP-1, -2, -3, -9 and -12 and their endogenous inhibitors (TIMPs), may play a role in the pathogenesis of venous hypertension and structuring of the venous wall (Buján J et al, 2000; Sansilvestri-Morel P et al, 2007; Sansilvestri-Morel P et al, 2005; Pascarella L et al, 2005; Woodside KJ et al, 2003; Zamboni P et al, 2005) (Herouy Y et al, 1998; Tarlton JF et al, 1999). Yet, there are no studies that have examined MMP activity over different time periods of venous pressure elevation to identify early versus later stage MMP expression patterns.…”
Section: Introductionmentioning
confidence: 99%